Respiratory Physiotherapy in Amyotrophic Lateral Sclerosis: A Systematic Review - Abal Monteagudo, Ruben; Da Cuña Carrera, Iria; Alonso Calvete , Alejandra; González González, Yoana (Archivos de Neurociencias, 2021)
Introduction: Amyotrophic lateral sclerosis is a central nervous system disease with a progressive degeneration of superior and inferior motor neurons, causing several complications, specially respiratory problems. Respiratory physiotherapy has a great importance in this disease, since it can improve considerably the pulmonary function and gases changes, increasing the air volumes and decreasing the respiratory work, facilitating then the elimination of bronchial secretions. Thus, the aim of this study is to review the scientific literature in the last 5 years about the physiotherapy in ALS patients. Development: A systematic review was carried out, searching in PubMed and Web of Science with the terms “amyotrophic lateral sclerosis” y “respiratory therapy”. 217 results were obtained, and after the inclusion and exclusion criteria 19 studies were selected. All works analyzed carried out different interventions in respiratory physiotherapy such as VNI, phrenic stimulation, Cough-Assist or exercise therapy. Conclusions: Respiratory physiotherapy seems to be effective for patients with ALS, except from phrenic stimulation.